A comparative experimental survey of the performance of new linearized transformations of the Butler-Volner equation for the corrosion rate assessment of AISI 316L stainless steel - Zoltán Lukács; Péter Benjamin Vidosits; Szabina Tomasek; Tamás Kristóf (Journal of Materials Research and Technology)
The conventional determination of electrochemical parameters of corrosion systems, first of all the corrosion rate, is based on the Butler-Volmer equation. A simplified method, based on the Stern-Geary equation, is typically used in industrial corrosion monitoring systems (Linear Polarization Resistance, LPR). Both methods have multiple sources of uncertainties that make the assessment of the corrosion rate erroneous. These error sources are even more expressed in the case of the measurement of stainless steel corrosion. Recently two linearized transformations of the Butler-Volmer equation were proposed in order to provide more accurate alternatives for the assessment of the corrosion rate. In this work these models are tested for the assessment of the corrosion rate of stainless steel 316L in neutral and acidic chloride solutions. The new models provide results consistent with each other, with conventional linearized semilogarithmic extrapolation and with literature data, indicating that the proposed new methods are applicable for the assessment of corrosion rate of stainless steels.